2012
DOI: 10.1515/secm-2012-0014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sugar cane bagasse ash as a cement replacement on properties of mortars

Abstract: Sugar cane bagasse ash (SCBA), a by-product of sugar and alcohol production, is one of the potential pozzolanic material that can be blended with Portland cement. In this study, SCBA with particle sizes < 45 μ m was used to replace type I ordinary Portland cement with various dosages (10 % , 20 % , and 30 % ) by weight of binder. The water/cementitious material (w/cm) and sand/binder ratios were kept at constants of 0.55 and 2.75, respectively. Composites were mixed, and effects of SCBA on properties were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…However, for mixes with SCBA and WPSA, the drying shrinkage values are lower than that of the control mix [111,112]. Mixes with 10% of SCBA, at 25-day, show a drying shrinkage of 8%, as low as that of OPC specimens.…”
Section: As Shown Inmentioning
confidence: 80%
See 3 more Smart Citations
“…However, for mixes with SCBA and WPSA, the drying shrinkage values are lower than that of the control mix [111,112]. Mixes with 10% of SCBA, at 25-day, show a drying shrinkage of 8%, as low as that of OPC specimens.…”
Section: As Shown Inmentioning
confidence: 80%
“…Mixes with 10% of SCBA, at 25-day, show a drying shrinkage of 8%, as low as that of OPC specimens. Thus, from the drying shrinkage point of view, 10 % of SCBA is found to be the optimal limit [111].…”
Section: As Shown Inmentioning
confidence: 93%
See 2 more Smart Citations
“…Zhang et al [14] studied the effect of a wheat husk ash, and they reported improvement of workability and compressive strength of concrete mixtures. Possibilities of utilization of a bagasse ash as SCM were studied by Chi [15] and also by Ganesan et al [16]. According to Ganesan et al, the best solution was found in 20% replacement, while Chi reported 10% as the best ratio of cement replacement.…”
Section: Introductionmentioning
confidence: 99%